QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2010)
Number of pages: 24

QFHSA Fall Conference 2010 - Quebec Federation of Home and School Associations (QFHSA) (2010)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2010)
Number of pages: 24

A Consultation - Quebec Federation of Home and School Associations (QFHSA) (2010)
The Quebec Federation of Home and School Associations Inc. welcomes the opportunity to present this consultation brief to the Standing Senate Committee on Official Languages.
Keywords: Official Language Minority Community (OLMC)

A Brief Presented to the Parliamentary Committee on the National Assembly on Bill 103 An Act to Amend the Charter of the French Language and Other Legislative Provisions - Quebec Federation of Home and School Associations (QFHSA) (2010)

Mémoire soumis à la Commission parlementaire de l'Assemblée nationale sur le projet de loi 103, loi modifiant la Charte de la langue française et d'autres dispositions législatives - Quebec Federation of Home and School Associations (QFHSA) (2010)

QFHSA News - Quebec Federation of Home and School Associations (QFHSA) (2010)
Number of pages: 24

66th Annual General Meeting & Conference - Quebec Federation of Home and School Associations (QFHSA) (2010)

Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (2010)
Parallel title: Building Our Future... Together!

Quebec Home & School News - Quebec Federation of Home and School Associations (QFHSA) (2010)
Number of pages: 16